2015
DOI: 10.1039/c4ob02466d
|View full text |Cite
|
Sign up to set email alerts
|

Benzosulfones as photochemically activated sulfur dioxide (SO2) donors

Abstract: Sulfur dioxide (SO2) is a gaseous environmental pollutant which is routinely used in industry as a preservative and antimicrobial. Recent data suggests that SO2 may have value as a therapeutic agent. However, due to its gaseous nature, localizing SO2 generation is challenging. Herein, various 1,3-dihydrobenzo[c]thiophene 2,2-dioxides (benzosulfones) were prepared as candidates for photochemically activated sulfur dioxide (SO2) generation. These compounds were found to be stable in buffer but were photolysed up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Chakrapani and colleagues have reported clever designs that utilize biological thiol (cysteine) and UV light to trigger the release of SO 2 gas from donors. 16, 17 They also developed elegant work on using benzosultines to generate SO 2 under physiological conditions. 18 Recently, Xian’s group reported benzothiazole sulfinate (BTS) as a pH dependent water soluble SO 2 donor.…”
mentioning
confidence: 99%
“…Chakrapani and colleagues have reported clever designs that utilize biological thiol (cysteine) and UV light to trigger the release of SO 2 gas from donors. 16, 17 They also developed elegant work on using benzosultines to generate SO 2 under physiological conditions. 18 Recently, Xian’s group reported benzothiazole sulfinate (BTS) as a pH dependent water soluble SO 2 donor.…”
mentioning
confidence: 99%
“…1-Phenyl-benzosulfone was found to be a more stable form of 1-phenyl-benzosultine ( 6 ) (Malwal et al, 2013 ). To develop UV light-triggered SO 2 prodrugs, Chakrapani's group further exploited the stability of benzosulfones (Malwal and Chakrapani, 2015 ). Three classes of benzosulfone were designed with varied substitution groups on the 1-position and the aryl ring ( 8 , Scheme 3 ).…”
Section: So 2 Donors and Prodrugsmentioning
confidence: 99%
“…SO 2 photoexpulsion from sulfolene has previously been observed, but is limited to triplet‐sensitized expulsions, [18] or to stepwise reactions forming stable biradical species which decay on to form products [19] . Studies of the triplet sensitized reaction initially indicated that the triplet state deactivates via intersystem crossing (ISC) to a vibrationally excited electronic ground‐state from which expulsion would occur.…”
Section: Introductionmentioning
confidence: 99%